2017
DOI: 10.1016/j.toxlet.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cyclin D1 by arsenic and microRNA inhibits adipogenesis

Abstract: Low-dose chronic exposure to arsenic in drinking water represents a global public health concern with established risks for metabolic and cardiovascular disease, as well as cancer. While the linkage between arsenic and disease is strong, further understanding of the molecular mechanisms of its pathogenicity is required. Previous reports demonstrated the ability of arsenic to interfere with adipogenesis, which may mediate its effects in promoting metabolic disease. We hypothesized that microRNA are important re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 55 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…CHOP10 is a protein that increases its expression in response to the stress of the endoplasmic reticulum produced by the incorrect folding of proteins. Similarly, Beezhold et al [50] showed that arsenic can increase the expression of microRNA, miR-29b, involved in the regulation of the cell cycle and in the increase in the expression of cyclin D1, which results in inhibition of the differentiation towards the fat cell.…”
Section: Heavy Metalsmentioning
confidence: 92%
“…CHOP10 is a protein that increases its expression in response to the stress of the endoplasmic reticulum produced by the incorrect folding of proteins. Similarly, Beezhold et al [50] showed that arsenic can increase the expression of microRNA, miR-29b, involved in the regulation of the cell cycle and in the increase in the expression of cyclin D1, which results in inhibition of the differentiation towards the fat cell.…”
Section: Heavy Metalsmentioning
confidence: 92%
“…C3H 10T1/2 preadipocytes exposed to sodium arsenite (6 mM) for 8 wk also experienced altered morphology and impaired differentiation (Trouba et al 2000). Arsenite-treated human hMSCs (1 lM for 24 and 48 h) exhibited significantly altered function of noncoding microRNA involved in adipogenesis (Beezhold et al 2017;Renu et al 2018). Both culture adipocytes and primary hMSCs isolated from mice treated with arsenite in vivo (100-250 ppb) increased microRNA 29 (miR-29) and cyclin D1 (CCND1) expression, furthering cell growth rather than adipogenic differentiation (Beezhold et al 2017).…”
Section: Adipose Tissue Functionmentioning
confidence: 99%
“…In consideration of their biological and epigenetic importance, disruptions in miRNA expression have been implicated in various diseases including cardiovascular disorders and cancer (Calin et al, 2005). Several studies have reported that arsenic exposure causes changes in miRNA expression (Marsit et al, 2006; Sturchio et al, 2014; Ren et al, 2016; Beezhold et al, 2017). Examples of arsenic-deregulated miRNAs include miR-29, -183, -192, etc.…”
Section: Introductionmentioning
confidence: 99%
“…42 Several studies have reported that arsenic exposure causes changes in miRNA expression. [43][44][45][46] Examples of arsenic-deregulated miRNAs include miR-29, -183, -192, etc. 45,46 Here we report for the first time that arsenic is able to trigger the down-regulation of miR-31, a known negative regulator of SATB2.…”
mentioning
confidence: 99%
See 1 more Smart Citation